TASKA AS THE FOUNDATION OF EARLY CHILDHOOD EDUCATION: IMPLEMENTING TEACHING AND LEARNING APPROACHES ALIGNED WITH PARENTS’ ASPIRATIONS - NUR AMIRA SYAZWANI ARSAD; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
The study examines the implementation of effective teaching and learning (T&L) approaches in taska that align with the expectations of modern families. Through a review of literature and previous studies, it is found that parents emphasize aspects such as safety, quality caregiving, holistic learning approaches, and the use of technology as key priorities. Various T&L approaches have been identified as suitable for infants and toddlers, including play-based learning, child-centred approaches, sensory-motor activities, the strengthening of social interactions, and active parental involvement in children’s developmental processes. Nevertheless, several challenges have been identified, including teachers’ competency levels, resource constraints, and communication gaps with parents. This article asserts that efforts to enhance educators’ professional training, strengthen taska-parent collaboration, and improve early education policies are essential to ensure that family aspirations are met. In conclusion, taska serves as a strong foundation for nurturing a balanced, creative and future-ready early generation prepared to face the challenges of the 21st century.